Vagus Nerve Stimulation Amplifies Task-Induced Cerebral Blood Flow Increase - Kunii, Naoto; Koizumi, Tomoyuki; Kawai, Kensuke; Shimada, Seijiro; Saito, Nobuhito (Frontiers in Human Neuroscience, 2021)
Background: Vagus nerve stimulation is an established palliative surgical treatment for refractory epilepsy. Recently, pairing vagus nerve stimulation with rehabilitation received growing attention for their joint effect on neural plasticity. However, objective biological measurements proving the interaction between vagus nerve stimulation effects and cortical recruitment are lacking. Studies reported that vagus nerve stimulation induced little blood flow increase in the cerebral cortex. Objective: This study tested the hypothesis that pairing vagus nerve stimulation with a cognitive task amplifies task-induced cerebral blood flow. Method: This study included 21 patients implanted with vagus nerve stimulator to treat refractory epilepsy. Near-infrared spectroscopy with sensors on the forehead measured cerebral blood flow changes in the frontal cortices in response to vagus nerve stimulation. Cerebral blood flow was measured when vagus nerve stimulation was delivered during a resting state or a verbal fluency task. We analyzed the vagus nerve stimulation effect on cerebral blood flow in relation to stimulation intensity and clinical responsiveness. Results: We observed no cerebral blood flow change when vagus nerve stimulation was delivered during rest, irrespective of stimulation intensity or responsiveness. Cerebral blood flow changed significantly when a verbal fluency task was paired with vagus nerve stimulation in a stimulation intensity-dependent manner. Cerebral blood flow changes in the non-responders showed no intensity-dependency. Conclusion: Our results could be an important biological proof of the interaction between vagus nerve stimulation effects and cortical recruitment, supporting the validity of pairing vagus nerve stimulation with rehabilitation.